2017
DOI: 10.1007/s12281-017-0275-8
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Flow Assays for the Diagnosis of Invasive Aspergillosis: Current Status

Abstract: Purpose of ReviewDiagnosis during early stages of invasive aspergillosis (IA) and targeted antifungal treatment has the potential to improve survival significantly. Despite advances in the diagnostic arsenal, invasive mold infections remain difficult to diagnose—especially at early stages before typical radiological signs develop. Varying availability and time-to-results are important limitations of current approved biomarkers and molecular assays for diagnosis of IA. Here, we will give an update on the Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…The clinical sensitivity of 71% and specificity of 100% found in this analysis is remarkable considering the BALF selection process, which comprised samples that gave false negative or false positive results with the old LFD. In other words, the performance of the old LFD with the BALF samples selected for this evaluation (64% sensitivity and 64% specificity), was inferior to the 73% sensitivity and 90% specificity published for the old BALF LFD over various patient cohorts, and also lower than the published performances of the old LFD in haematological malignancy patients (sensitivity 67%, specificity 91%; total n = 193 samples), and ICU patients (sensitivity 79%, specificity 85%; total n = 239 samples) …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The clinical sensitivity of 71% and specificity of 100% found in this analysis is remarkable considering the BALF selection process, which comprised samples that gave false negative or false positive results with the old LFD. In other words, the performance of the old LFD with the BALF samples selected for this evaluation (64% sensitivity and 64% specificity), was inferior to the 73% sensitivity and 90% specificity published for the old BALF LFD over various patient cohorts, and also lower than the published performances of the old LFD in haematological malignancy patients (sensitivity 67%, specificity 91%; total n = 193 samples), and ICU patients (sensitivity 79%, specificity 85%; total n = 239 samples) …”
Section: Discussionmentioning
confidence: 57%
“…The ease‐of‐use of the assay, requiring no pretreatment of bronchoalveolar lavage fluid (BALF), allows point‐of‐care testing, with results available within 15 minutes. To date, a prototype version of the test has been evaluated with more than 650 BALF samples across a number of studies, with an overall sensitivity of 73%, specificity of 90%, a positive predictive value (PPV) of 61%, and negative predictive value (NPV) of 94% for probable/proven IPA vs no IPA . As with other diagnostic tests for IPA such as the galactomannan [GM] ELISA, LFD sensitivity is reduced by mould‐active antifungal drugs .…”
Section: Introductionmentioning
confidence: 99%
“…Grancini et al suggested that BAL real‐time PCR, when performed in conjunction with routine BAL culture and GM, can have a NPV of 99% in immunocompromised patients, while Hoenigl et al reported 100% sensitivity and 98% specificity when combining PCR with GM. Point of care lateral‐flow device tests to detect an extracellular glycoprotein antigen secreted by Aspergillus spp in blood and urine are currently being developed and validated for adjunctive use in rapid diagnosis of IA. Mould‐specific microbial volatile signatures can be detected in patient breath, potentially leading to early and accurate bedside diagnosis of IMI …”
Section: Discussionmentioning
confidence: 99%
“…The conclusion from these studies was that prototype LFD had high specificity and NPV, but only modest sensitivity and PPV. However, a recent review noted sensitivity as high as 73% when results from the various studies were combined …”
Section: Discussionmentioning
confidence: 99%